Studies on Variability and Character Association in Moth Bean - Jindal, S K; Vir, Satya (Annals of Arid Zone, 2016)
A study was undertaken to determine the extent of genetic variability for grain yield and seven other quantitative characters, interrelationship of these characters and the cause and effect relationship of grain yield with other characters in 22 strains of moth bean. Strong correlation of yield with pods/ plant, pod length, seeds/pod, plant height, clusters/plant and 1OO-seed weight were observed. The path-coefficient analysis indicated that pod length and pods/plant exerted positive direct effects on grain yield.